Big Data and Social Media Qualitative Research Methodology - Chongthanavanit, Papon; Kennedy , John M.; Kheokao , Jantima (Thammasat Review, 2020)
The paper demonstrates and evaluates a methodology for conducting big data and social media research using qualitative methods. Large-scale databases of customer-generated content in social media have captured scientific attention, producing an abundance of valuable information. However, only a few studies have used a qualitative approach to analyze big data. This paper presents the step by step process of managing big data and qualitative analyses integrating computational approaches. It is based on a study of dental tourism in Thailand as a case example to validate as well as to highlight the advantages and limitations of the methodology.